Analisis Kinerja Keuangan Pemerintah Daerah Kabupaten Tebo - Miftakur Rohmad; As’ad Isma; Fauzan Ramli (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2023)
Performance measurement is very important to assess how well organizations and managers are in providing more public services, and not just the ability to show that public money has been spent but includes the ability to show that the money has been used fairly, for the welfare of society. Then, from the background above, this study aims to analyze how the Bakeuda Financial Performance of the Tebo Regency Government in 2017-2021 is seen from: (1) Independence Ratio, (2) Efficiency Ratio (3) Harmony Ratio (operational expenditure and capital expenditure). This study uses a quantitative descriptive analysis method, which is a scientific and systematic study of the parts and phenomena and their relationships. Quantitative analysis is used to solve problems that are measuring quality in the form of (amount and number). The results of the performance analysis show that the Tebo Regency Government's Bakeuda finances are seen from (1) the Regional Financial Independence Ratio, the relationship pattern is still classified as an instructive relationship pattern because the average size of this ratio is 9.78% (2) The Regional Financial Efficiency Ratio can be said to be quite efficient because the average regional financial efficiency of Blora Regency is 88.26% (3) The compatibility ratio is known that the average regional operational expenditure is still very high, namely 56.35% compared to the average capital expenditure of 39.92%, so it can be said Regional Government still pays little attention to regional development.